IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA KELAS XI DI SMA MUHAMMADIYAH 1 PALANGKA RAYA - Anggraini, Vera; Karliani, Eli; Mustika, Maryam (Yayasan Education and Social Center, 2024)
This research aims to describe and analyze the forms of implementation, obstacles and efforts in implementing the project to strengthen the profile of class XI Pancasila students at SMA Muhammadiyah 1 Palangka Raya. This research uses qualitative methods with descriptive research type. Research subjects included the Principal of SMA Muhammadiyah 1 Palangka Raya, Deputy Principal of SMA 1 Palangka Raya for curriculum, P5 Coordinator, P5 class XI facilitator, and three class XI students. Data was collected through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the project to strengthen the profile of Pancasila students at SMA Muhammadiyah 1 Palangka Raya includes the themes of local wisdom and entrepreneurship. P5 implementation is carried out in three stages: planning, implementation, and evaluation. Obstacles faced include students who are less active, time constraints, and costs. Efforts made include giving appreciation to active students, dividing tasks, using time effectively, adding project lesson hours, and submitting funding proposals. The school also provides adequate facilities and infrastructure as well as facilitator teachers who are ready to guide each activity